EFEKTIFITAS PRAKTIKUM BIOKIMIA BERBASIS LABORATORY VIRTUAL DI MASA PANDEMI COVID-19: STUDI KOMPARASI PRAKTIKUM LURING DAN DARING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI PROTEIN PADA MAHASISWA - Rina Astuti; Gakuh Munia Setianingsih; Samia Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2021)
Abstract:. Learning held in tertiary institutions must be in line with the 21st century learning paradigm, where students are expected to be active and creative in developing their potential. The nature and characteristics of 21st century learning are reflected in science learning which refers to 3 things such as processes, products and attitudes which can be seen in practicum-based learning methods. This study aims to compare the results of practicum during the Covid-19 pandemic which was conducted online and during offline, namely before the pandemic that hit Indonesia and even the world. The method used is a quasi-experimental method with the comparison method. The analysis used in this study was the independent sample t-test where the subjects were students with different classes and were given two different learning treatments, namely offline and online. The results showed that the real or offline practicum was better and more effective than the internal practicum. network (online).